Buah Mengkudu (Morinda citrifolia) Meningkatkan Respon Imun Mencit (Mus musculus) Terhadap Infeksi Bakteri Staphylococcus aureus - Zumrotul, Mufidah (Unusa Press, 2013)
Noni (Morinda citrifolia) Increase Immune Response in Mice (Mus musculus) Infected Staphylococcus aureus. Infection disease caused by bacteria is one of the illness in several developing countries including in Indonesia, with high mortality rate. Infection of  S. aureus as the cause of problem resistance for antibiotic or multi drug resistance are giving the therapy of drug itself with change to medical herbal. The aim of this study is known the role of M.citrifoliaextract to increase immune response of mice with infectioned of S. aureus. Mice were divided into two groups there are Non Infection and infection. Non Infection is without S. aureus and than infection has S. aureus. The each groups are including control, dose 1 (25 mg/kg BW), dose 2 (100 mg/kg BW), and dose 3 (300 mg/kg BW). Relative number of lymphocyte T cell (CD4+) subsets was measured  using the BD FACSCaliburTM Flowcytometer. Data were analyzed using Analysis of Varians (p<0,05) and using SPSS 16 for windows. The result showed that administration of  M. citrifolia crude extract in non infection groups was significantly increase the relative amounts T cell subsets (CD4+). Noni fruit extract can used as prevention therapy on infection disease of S. aureus bacteria because it contains active compounds that are anti-inflammationMengkudu